IMPLEMENTASI PROGRAM KUPAT DALAM MENINGKATKAN KEDISIPLINAN PENGUMPULAN TUGAS SISWA SEKOLAH DASAR - Riswanto; Wildan Nurul Fajar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the design, implementation, obstacles, and impact of the KUPAT Program (Kumpulkan Tugas Tepat Waktu/Submit Assignments on Time) in building discipline and responsibility character among elementary school students at SD Negeri Sidamulya 03 Sidareja. The program was developed in response to three identified root problems: lack of parental supervision due to work demands, students' low ability to manage study time, and the absence of a disciplined culture in task completion. This study employed a qualitative descriptive approach with a single case study design. Data were collected through direct classroom observation, task submission control sheets, weekly reflection activities, program documentation, and communication with parents via liaison books. Data analysis followed the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The findings indicate that the KUPAT Program, which utilizes the "Pohon KUPAT" visual media, sticker-based reward systems, and weekly reflective activities, effectively increased the number of students submitting assignments on time. Beyond surface-level behavioral change, the program produced broader character improvements across ten observed dimensions, including learning independence, social awareness, self-confidence, and a sense of responsibility. Five theoretical frameworks were found to operate synergistically in explaining the program's success: Skinner's behaviorism, Bandura's social learning theory, character habituation principles, constructivism, and Bronfenbrenner's ecological theory. However, the study is limited in scope to one classroom over one semester, with potential observational subjectivity. Future research is recommended to strengthen data triangulation, measure the long-term sustainability of behavioral change, and replicate the model across diverse school contexts.